MODERN METHOD OF DETECTING VOLATILE METABOLITES OF BIOGENIC AMINES IN MYOCARDIAL INFARCTION - G. I. Kodirova (Scholar Express Journals, 2023)
The volatile metabolits of biogenical amins of exhaled air were studied for the first time, the functional activity of sympatic-adrenal system on the excretion of combined and free fractions of catecholamins and DOFA in daily urine was studied simultaneously. It is shown the results of the investigation on the new methods of noninvasing diagnosing of Ischemic Heart disease in this paper. This method is based on analyzes of expirating air. The results of investigation showed the possibility of the surface ionizating detector in diagnosis of Ischemic Heart disease. It was revealed the statisticly importance of difference in containing the amines in expirating air of patients ill with Ischemic Heart disease and healthy people. The advantage of this method concludes whole harmless, expressive ness and canceling the operative intervention and possibilities of mass testing, and cheap price of observation. The difference in eliminating the amines with expirating air can be stable marker for early diagnosing of the preinfarctive state
Keywords: cardiovascular disease; coronary heart disease; sympathetic-adrenal system